Medical professionalism – who cares? - Walmsley, Claire (Clin Med (Lond), 2006)
Who cares about medical professionalism? It seems doctors, patients and, surprisingly, the media do. The relevance of medical professionalism for these three groups is examined from the journalist's/patient's point of view. The report and findings of the Royal College of Physicians Working Party on Medical Professionalism is discussed. In conclusion there is a synopsis of recommendations and future action required by individuals from all three groups to enable progress to be made in this important area of communication.